Desenvolvimento e avaliação biológica de sistemas nano- e microparticulados contendo 3,3’-diindolmetano - Mattiazzi, Juliane (2019)
3,3’-Diindolylmethane (DIM) is a phytochemical compound originated after the ingestion of some vegetables. Despite the several health benefits showed by this bioactive (like antioxidant, anti- inflammatory and antineoplasic effects), it is water-insoluble, presenting oral bioavailability of 1% and it is thermo and photolabile, which restrains its pharmaceutical applications. In attempt to overcome these issues and improve DIM therapeutic potential, an interest approach is the incorporation of the compound in polymeric microparticles (MPs) or nanocapsules (NCs), which provide protection of the drug and improved dissolution profile for hydrophobic substances. Therefore, this thesis aimed to the development of DIM-loaded MPs. The in vitro photostability, antioxidant and antitumoral (glioma cells) actions of NCs were assessed as well as the evaluation of DIM antinociceptive effect, in its free or nano/microencapsulated forms, using animal models of acute pain. The Ethical Research Committee of Federal University of Santa Maria approved all experimental procedures carried out in the present study, which are register under the nº 4428090217/2017. The NCs suspensions were prepared by the interfacial deposition of pre-formed polymers and demonstrated suitable physicochemical characteristics: particles in nanometric diameter (100-300 nm), polydispersity indexes below 0.25, positive or negative zeta potentials depending on the polymer feature, acid pH, drug content close to the theoretical (1 mg/mL) and encapsulation efficiency about 100%. In the photostability assay, after 5h under UVC exposure, NCs presented DIM content 3-fold higher than free DIM (methanolic solution). The DIM release from the NCs was evaluated by the dialysis bag technique, demonstrating that the NCs prolonged the DIM release, which fits first order kinetic and anomalous transport as release mechanism. For DIM scavenging capacity test, the DPPH or ABTS reagents were added to NC samples containing 2-4-6 µg/mL of DIM. DIM presented scavenging activity in both free and nanoencapsulated forms, which was more pronounced for the NCs. The cytotoxic effect of free DIM or DIM-loaded NCs against U87 human glioblastoma cells was performed at 3-6-12-24 μg/mL and demonstrated that nanoencapsulation generally enhanced the antitumor effect of DIM (Article 1). Besides, it was demonstrated the feasibility of preparation of DIM-loaded MPs, which have shown suitable physicochemical characteristics, as micrometric diameter (200-400 µm), narrow size distribution, DIM content of 150 mg/g and encapsulation efficiency of 84%, as well as controlled release of the active. Other physicochemical evaluations demonstrated that NCs and MPs were able to adequately encapsulate DIM without interactions of the active with the other materials of the formulations. In addition, the antinociceptive effect was evaluated using distinct animal models of acute pain (Thermic nociception model - Hot plate; Chemical nociception model induced by formalin; Model of acute inflammatory pain induced by Complete Freund’s Adjuvant). Male Swiss mice (25-35 g) were intragastrically treated (DIM doses of 2,5, 5 ou 10 mg/Kg) and the behavioral tests were performed after 0,5-8h. The results demonstrated DIM antinociceptive/anti-hypernociceptive action, in both free and nano/microencapsulated forms, presenting prolonged and enhanced effect in the NCs or MPs in comparation with the free form (Manuscripts 1 and 2). Therefore, the present work showed the feasibility of preparation of DIM-loaded NCs and MPs, in addition to the ability of these systems of promoting DIM prolonged release and photoprotection, as well as improve the antinociceptive and antioxidant activity this bioactive, consisting in an innovative approach to DIM oral delivery for pain management .